The rise and fall of income inequality in Mexico: 1989 - 2010 - Raymundo Campos; Gerardo Esquivel; Nora Lustig (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Inequality in Mexico rose between 1989 and 1994 and declined between 1994 and 2010. We examine the role of market forces (demand and supply of labour by skill), institutional factors (minimum wages and unionization rate), and public policy (cash transfers) in explaining changes in inequality. We apply the re-centred influence function method to decompose changes in hourly wages into characteristics and returns. The main driver is changes in returns. Returns rose (1989-94) due to institutional factors and labour demand. Returns declined (1994-2006) due to changes in supply and, to a lesser extent, in demand; institutional factors were not relevant. Government transfers contributed to the decline in inequality, especially after 2000.
Keywords: D31; J20; J31; O54; 330; inequality; wages; disposable income; labour markets; Mexico; Einkommensverteilung; Arbeitsmarkt; Mindestlohn; Gewerkschaftsmitgliedschaft; Öffentliche Sozialleistungen; Mexiko